Pros and cons of initial public offerings - Chan, Joseph Wai Meng (2014)
The objective of this paper is to explain the pros and cons of going public as well as the factors considered by the firms in their decision making process. This study attempts to highlight the actual costs and benefits considered by the firms and their relative importance as perceived by the firms. To achieve this objective, 67 questionnaires were sent out to Singapore companies that have gone public in the last 7 years, from 1987 to 1993. The questionnaire provided a list of the costs and benefits which we feel may be important. The financial controllers of the firms, to whom the questionnaires were addressed, would then rank the relative importance of these factors.